2007
DOI: 10.1016/j.rmed.2007.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Differences in exhaled breath condensate pH measurements between samples obtained with two commercial devices

Abstract: The present study demonstrates that EBC pH value is dependent on the collection device used and that the storage for 8 weeks had a significant influence on the pH of samples analyzed without deaeration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 17 publications
1
53
1
1
Order By: Relevance
“…This superiority of glass coatings may be mainly related to the behaviour of water as bipolar vehicle [4]. Three other studies report the influence of sampling systems on biomarkers in EBC [28][29][30]. TUFVESSON and BJERMER [28] proposed to coat EcoScreen1 collection surfaces with bovine serum albumin and Tween-20, to measure cytokines and eicosanoids, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This superiority of glass coatings may be mainly related to the behaviour of water as bipolar vehicle [4]. Three other studies report the influence of sampling systems on biomarkers in EBC [28][29][30]. TUFVESSON and BJERMER [28] proposed to coat EcoScreen1 collection surfaces with bovine serum albumin and Tween-20, to measure cytokines and eicosanoids, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…SOYER et al [29] found significantly higher cysteinyl leukotrienes and eotaxin using EcoScreen1, compared with RTube TM , due to susceptibility of pre-cooled RTube TM sleeves to (increased) ambient temperatures during collection, and due to different materials that could affect sample recovery. PRIETO et al [30] compared RTube TM and EcoScreen1, and reported that EBC pH values are dependent on the collection device used. Furthermore, the EcoScreen1 has been associated with deposition of frozen condensate on its lamellar walls.…”
Section: Discussionmentioning
confidence: 99%
“…The commercially available EcoScreen (Jaeger, Wurzburg, Germany) and R-tubes (Respiratory Research Inc., Charlottesville, VA, USA) are commonly used, while some laboratories have used their own custom-made devices. Studies comparing collection devices have shown that there may be differences; in a mixed group of patients with asthma or allergic rhinitis and healthy volunteers, significantly higher pH levels were observed in EBC collected using EcoScreen compared to R-tubes [6]. Significantly higher eotaxin and cysteinyl-leukotriene levels have also been observed using the EcoScreen compared to R-tubes [7].…”
Section: Ebc Collection Collection Devicementioning
confidence: 99%
“…It is considered to be the most validated parameter of EBC, which can be easily and reproducibly measured with non-expensive equipment (1). There are certain limitations and unresolved questions, including the source of airway acidifi cation assessed by EBC pH, issues regarding the methodology of EBC collection, sample preparation and EBC pH measurement, as well as sensitivity and specifi city of the method (8)(9)(10)(11)(12). Nevertheless, a number of studies have shown that acidifi cation caused by the infl ammation of the airways, like in asthma or chronic obstructive pulmonary disease, is refl ected in lower EBC pH (8).…”
mentioning
confidence: 99%